2023
DOI: 10.3390/biomedicines11123201
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid Aptamer-Based Biosensors: A Review

Beatriz Sequeira-Antunes,
Hugo Alexandre Ferreira

Abstract: Aptamers, short strands of either DNA, RNA, or peptides, known for their exceptional specificity and high binding affinity to target molecules, are providing significant advancements in the field of health. When seamlessly integrated into biosensor platforms, aptamers give rise to aptasensors, unlocking a new dimension in point-of-care diagnostics with rapid response times and remarkable versatility. As such, this review aims to present an overview of the distinct advantages conferred by aptamers over traditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 155 publications
0
3
0
Order By: Relevance
“…154 Aptamer-based biosensors are used in clinical diagnostics 155,156 to identify therapeutic medication levels in patient samples, guaranteeing appropriate dosage and effective treatment. 157 Pharmacological analysis is made easier by biomimetic receptors, especially MIPs, which guarantee the quality and purity of drug formulations. MIPs are used to extract active pharmacological ingredients (APIs) from complicated matrices in a selective manner.…”
Section: Applications Of Aptamers and Biomimetic Receptors In Biosensingmentioning
confidence: 99%
“…154 Aptamer-based biosensors are used in clinical diagnostics 155,156 to identify therapeutic medication levels in patient samples, guaranteeing appropriate dosage and effective treatment. 157 Pharmacological analysis is made easier by biomimetic receptors, especially MIPs, which guarantee the quality and purity of drug formulations. MIPs are used to extract active pharmacological ingredients (APIs) from complicated matrices in a selective manner.…”
Section: Applications Of Aptamers and Biomimetic Receptors In Biosensingmentioning
confidence: 99%
“…The ease of engineering and customization further enhances their adaptability across various domains [ 71 ]. These versatility and cost-effective synthesis methods position aptamers as valuable tools in biomedical diagnostics, therapeutics, and diverse scientific disciplines, contributing to their widespread impact [ 72 ].…”
Section: Aptamers: General Conceptsmentioning
confidence: 99%
“…Nucleic acid aptamers refer to a class of single-stranded DNA or RNA oligonucleotide sequences that can be rapidly synthesized in vitro and possess specific binding capabilities to target molecules . The previous research reported the detection of an aptasensor for exosome electrochemical or fluorescence analysis methods.…”
Section: Introductionmentioning
confidence: 99%